2019
DOI: 10.1016/j.neuropsychologia.2017.02.012
|View full text |Cite
|
Sign up to set email alerts
|

Brain structural correlates of executive and social cognition profiles in behavioral variant frontotemporal dementia and elderly bipolar disorder

Abstract: An early stage of behavioral variant frontotemporal dementia (bvFTD) often displays a mix of behavioral disturbances and personality changes hindering a differential diagnosis from elderly bipolar disorder (BD), making this process a big challenge. However, no studies have compared these pathologies from neuropsychological and neuroanatomical perspectives. The aim of the present study was to compare the executive functions (EF) and social cognition profiles as well as the structural neuroimaging of bvFTD and e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
78
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 71 publications
(90 citation statements)
references
References 95 publications
(121 reference statements)
10
78
1
1
Order By: Relevance
“…Our findings corroborate previous studies of marked impairment in the domain of social cognition in patients with bvFTD (Adenzato, Cavallo, & Enrici, 2010;Baez et al, 2017;Cavallo, Enrici, & Adenzato, 2011;Dermody et al, 2016;Eslinger et al, 2007;Gregory et al, 2002;Irish, Hodges, & Piguet, 2014;Lough, Gregory, & Hodges, 2001;Lough & Hodges, 2002;Lough et al, 2006;Snowden et al, 2003;Torralva et al, 2007) and suggest that communicative intentions are disproportionately affected in bvFTD.…”
Section: Discussionsupporting
confidence: 92%
“…Our findings corroborate previous studies of marked impairment in the domain of social cognition in patients with bvFTD (Adenzato, Cavallo, & Enrici, 2010;Baez et al, 2017;Cavallo, Enrici, & Adenzato, 2011;Dermody et al, 2016;Eslinger et al, 2007;Gregory et al, 2002;Irish, Hodges, & Piguet, 2014;Lough, Gregory, & Hodges, 2001;Lough & Hodges, 2002;Lough et al, 2006;Snowden et al, 2003;Torralva et al, 2007) and suggest that communicative intentions are disproportionately affected in bvFTD.…”
Section: Discussionsupporting
confidence: 92%
“…On LILACS, none of the nine retrieved met the requirements. Therefore, 42 articles were selected, of which 10 were cohort studies 15,16,17,18,19,20,21,22,23,24 , three were case-control studies 25,26,27 , 12 were case repo rts 28,29,30,31,32,33,34,35,36,37,38,39 and 17 other studies were cross-sectional surveys 6,7,40,41,42,43,44,45,46,47,48,49,50,51,52,53,54 .…”
Section: Resultsmentioning
confidence: 99%
“…Nevertheless, they found that specific CSF biomarkers-total tau, phosphorylated tau, amyloid-β 1-42 peptide and neurofilament light chain concentrations-may aid clinicians in the diagnostic workup (64). Also, in an attempt to contribute to the distinction between primary psychiatric disorders and bvFTD, Metin and colleagues used quantitative electroencephalography for differentiating bvFTD from late-life BD with 76% overall accuracy 41 .…”
Section: Psychiatric Presentations In Bvftdmentioning
confidence: 99%
“…En nuestro estudio, el IFS ha demostrado ser una buena herramienta clínica con propiedades psicométricas que muestran buena consistencia interna y validez discriminante para determinar el funcionamiento ejecutivo en adicciones; previamente, Torralva y colaboradores habían confirmado las cualidades psicométricas de la prueba en la demencia tipo alzhéimer y demencia frontotemporal (Torralva, Roca, Gleichgerrcht, Bekinschtein et al, 2009;Torralva, Roca, Gleichgerrcht, López et al, 2009), y Báez e Ibáñez reportaron las ventajas del instrumento para identificar la disfunción ejecutiva en el trastorno afectivo bipolar (Báez et al, 2014(Báez et al, , 2017. Si bien, evaluar el funcionamiento ejecutivo en su totalidad es complejo y el uso de una sola batería neurocognitiva no permitiría sensibilizar con exactitud todos los dominios ejecutivos, el uso del IFS resulta ser una excelente herramienta clínica para el diagnóstico del funcionamiento ejecutivo, privilegiando, además, los tiempos de aplicación y la sencillez del protocolo.…”
Section: Discussionunclassified